2017
DOI: 10.1016/j.psyneuen.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal cortisol concentrations predict neurodevelopment in middle childhood

Abstract: Glucocorticoids (cortisol in humans) are the end product of the hypothalamic-pituitary-adrenocortical (HPA) axis and are proposed as a key mechanism for programming fetal brain development. The present prospective longitudinal study evaluates the association between prenatal maternal cortisol concentrations and child neurodevelopment. Participants included a low risk sample of 91 mother-child pairs. Prenatal maternal plasma cortisol concentrations were measured at 19 and 31 gestational weeks. Brain development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 71 publications
(108 reference statements)
1
74
0
Order By: Relevance
“…However, the direction of the associations they reported is the reverse of those found in the present study. Interestingly, the present results are consistent with the direction of the effects reported by Davis and Sandman (2010), who found that elevated levels in later pregnancy predicted higher levels of mental development scores (see also Davis et al, 2017). However, unlike our results and those of Huizink et al (2003), significant associations between higher late-pregnancy cortisol and greater mental development scores were not apparent until the age of 12-months in Davis and Sandman’s (2010) study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the direction of the associations they reported is the reverse of those found in the present study. Interestingly, the present results are consistent with the direction of the effects reported by Davis and Sandman (2010), who found that elevated levels in later pregnancy predicted higher levels of mental development scores (see also Davis et al, 2017). However, unlike our results and those of Huizink et al (2003), significant associations between higher late-pregnancy cortisol and greater mental development scores were not apparent until the age of 12-months in Davis and Sandman’s (2010) study.…”
Section: Discussionsupporting
confidence: 92%
“…In this case, the effect was conjectured to depend on early versus late fetal exposure to GCs due to the sensitivity of hippocampal differentiation occurring around 16 weeks of gestation and synaptic pruning in the prefrontal cortex occurring between 26 and 34 weeks of gestation (Waters, West, & Mendes, 2014). Similarly, higher levels of maternal cortisol in the third trimester, especially, were found to be associated with increased cortical thickness, particularly in areas of the frontal lobe, in their 6- to 9-year-old children (Davis, Head, Buss, & Sandman, 2017). Higher levels of third trimester maternal cortisol were also associated with better performance on the Wechsler Intelligence Scale for Children IV and the Expressive Vocabulary Test, Second Edition (Wechsler, 2002; Williams, 2007; Davis et al, 2017).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Maternal depression was negatively associated with cortical thickness with the association significantly stronger in girls than boys [52]. Finally, Davis et al ( N  = 91) found significant associations between third trimester maternal cortisol concentrations and brain development, but no evidence of sex dependence [33]. …”
Section: Resultsmentioning
confidence: 99%
“…Investigators from the Rhea Study ( N  = 288) found no evidence for sex dependence in the association between PNMS and child cognitive development at age 4 [27]. Davis et al ( N  = 91) found no evidence of a sex-dependent association between maternal prenatal plasma cortisol concentrations and child (ages 6–9) cognitive functioning [33]. Finally, data from two independent cohorts ( N = 6969 and N  = 425) provided no evidence of sex dependence in an association between prenatal maternal anxiety and offspring working memory [23].…”
Section: Resultsmentioning
confidence: 99%